Built Heritage Research and History of Architecture: Light and Acoustic in the Cistercian Monastic Church of S. Bento de Cástris (Portugal) - Martins, Ana Maria Tavares (2020)
Submitted by (amtfm@ubi.pt) on 2020-01-21T22:54:53Z No. of bitstreams: 1 2019_IOP_Conf._Ser.__Mater._Sci._Eng._603_022054.pdf: 1257922 bytes, checksum: c0cff1d31d089861f26a5e4d300c17d1 (MD5)